1955
DOI: 10.1152/ajplegacy.1955.184.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Vascular and Extravascular Protein Exchange in Unbled and Bled Dogs

Abstract: Unanesthetized, healthy greyhounds were infused with 25% albumin or bled, injected with I131-labeled albumin and albumin specific activities determined. It is shown that the albumin specific activity curves can be altered by changing the ratio of the vascular to extravascular albumin masses in a manner predicted from the mathematics of a two-compartment system. Increase of vascular albumin mass relative to extravascular mass results in a smaller initial disappearance of albumin specific activity from the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1957
1957
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Slight increases in plasma volume play some part in this but more importantly a greater proportion of total body albumin mass is lost from the extravascular space rather than from the plasma. These observations substantiate those of many other workers using different techniques and a wide variety of experimental subjects ( In protein malnutrition the alterations described are a consequence of lowered albumin synthetic rates but similar reductions in extravascular albumin mass also occur after plasmapheresis (Yuile, Lucas, Neubecker, Cochrane & Whipple, 1959; Matthews, I 961) and haemorrhage (Wasserman, Joseph & Mayerson, 1956) when presumably synthetic rates are normal or elevated, and consequently James & Hay (1968) suggested that a fall in extravascular albumin mass is related to the depletion of the intravascular mass and not to the process by which this occurs; any explanation offered for the redistribution of whole body albumin mass in protein deficiency should take this point into account.…”
Section: Total Body Albumin Mass and Distributionsupporting
confidence: 87%
“…Slight increases in plasma volume play some part in this but more importantly a greater proportion of total body albumin mass is lost from the extravascular space rather than from the plasma. These observations substantiate those of many other workers using different techniques and a wide variety of experimental subjects ( In protein malnutrition the alterations described are a consequence of lowered albumin synthetic rates but similar reductions in extravascular albumin mass also occur after plasmapheresis (Yuile, Lucas, Neubecker, Cochrane & Whipple, 1959; Matthews, I 961) and haemorrhage (Wasserman, Joseph & Mayerson, 1956) when presumably synthetic rates are normal or elevated, and consequently James & Hay (1968) suggested that a fall in extravascular albumin mass is related to the depletion of the intravascular mass and not to the process by which this occurs; any explanation offered for the redistribution of whole body albumin mass in protein deficiency should take this point into account.…”
Section: Total Body Albumin Mass and Distributionsupporting
confidence: 87%
“…The immediate fall in the extravascular activity in phase 2 is associated with a fall in the albumin synthetic rate. Plasmapheresis or bleeding of animals on normal protein intakes, with presumably normal or increased synthetic rates, also produces a fall in extravascular mass (47,48). This suggests that the shift in albumin into the intravascular compartment is related to the depletion of intravascular albumin mass per se, and not to the process by which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…This would be in agreement with the results of some other workers. Wasserman, Joseph and Mayerson (17) conclude from plasmapheresis and infusion experiments in dogs that albumin is first replaced from the extravascular pool and later by increased synthesis. Rodionov and associates (16) reach the same conclusions from plasmapheresis experiments in dogs with and without liver denervation, but they also find a large increase in globulins after bleeding.…”
Section: Discussionmentioning
confidence: 99%